State of the world 2018: democracy facing global challenges*. Issue 6 (18th August 2019) - Lührmann, Anna; Grahn, Sandra; Morgan, Richard; Pillai, Shreeya; Lindberg, Staffan I.
ABSTRACT: This article analyses the state of democracy in the world in 2018, and recent developments building on the 2019 release of the V-Dem dataset. First, the trend of autocratization continues and 24 countries are now affected by what is established as a "third wave of autocratization". Second, despite the global challenge of gradual autocratization, democratic regimes prevail in a majority of countries in the world (99 countries, 55%) in 2018. Thus, the state of the world is unmistakably more democratic compared to any point during the last century. At the same time, the number of electoral authoritarian regimes had increased to 55, or 31% of all countries. Third, the autocratization wave is disproportionally affecting democratic countries in Europe and the Americas, but also India's large population. Fourth, freedom of expression and the media, and the rule of law are the areas under attack in most countries undergoing autocratization, but toxic polarization of the public sphere is a threat to democracy spreading across regimes. Finally, we present the first model to predict autocratization ("adverse regime transitions") pointing to the top-10 most at-risk countries in the world.